Low-temperature architecture of a cubic-phase CsPbBr3 single crystal for ultrasensitive weak-light photodetectors. Issue 63 (16th July 2021) - Wei, Xiangfeng; Liu, Han; Zhang, Zhixiang; Xu, Wenchao; Huang, Wenjun; Luo, Lin-Bao; Liu, Jiehua
Abstract : Cubic-phase CsPbBr3 single crystals are synthesized by regulating H2 O with CsBr/PbBr2 in a ratio of 1 : 1 at low temperature by the freezing method. The CsPbBr3 single-crystal photodetector exhibits a superior weak-light responsivity of 278 A W −1 . Abstract : We present the first report of a water-regulated method for obtaining a cubic-phase CsPbBr3 single crystal that could be frozen at low temperature with a CsBr/PbBr2 ratio of 1 : 1. The cubic CsPbBr3 single-crystal photodetector exhibits a superior responsivity of 278 A W −1, an EQE of 6.63 × 10 4 %, and an ultrahigh detectivity of 4.36 × 10 13 Jones under low-power 520 nm irradiation at 3 V.